Orthodontic treatment provision and referral preferences among New Zealand general dental practitioners - Aldawood S.; Ampuan S.N.H; Medara N.; Thomson W.M (Sciendo, 2011)
Background: General dental practitioners (GDPs) are key clinicians in the orthodontic referral chain as they complement (and may compete with) orthodontists in providing treatment for the public.